Ganesh idol at Ganapati Temple - Ghosh, Ayan (2023)
This nine-inch-tall Ganesha idol is worshipped at the Ganapati Temple. It is made of white marble quarried from Rajasthan and is enclosed in a glass casing. The shrine is made from wood and has a dome similar to the dome on top of the temple.